2013
DOI: 10.1371/journal.pone.0081944
|View full text |Cite
|
Sign up to set email alerts
|

A Coastal Seawater Temperature Dataset for Biogeographical Studies: Large Biases between In Situ and Remotely-Sensed Data Sets around the Coast of South Africa

Abstract: Gridded SST products developed particularly for offshore regions are increasingly being applied close to the coast for biogeographical applications. The purpose of this paper is to demonstrate the dangers of doing so through a comparison of reprocessed MODIS Terra and Pathfinder v5.2 SSTs, both at 4 km resolution, with instrumental in situ temperatures taken within 400 m from the coast. We report large biases of up to +6°C in places between satellite-derived and in situ climatological temperatures for 87 sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
113
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 58 publications
(111 reference statements)
8
113
2
Order By: Relevance
“…In addition, previous studies have demonstrated biases in SST data when comparing it to in situ measurements within coastal areas (Smale and Wernberg, 2009;Lathlean et al, 2011;Stobart et al, 2016), with some studies recording up to 6 • C differences (Smit et al, 2013). These biases are due to contamination of the satellite processing due to the presence of coastal features such as the shoreline, estuaries and embayments as well as complex coastal dynamics such as tides and upwelling (Smit et al, 2013) that vary over short spatial scales. Despite this well documented bias of satellite SST data in coastal areas, no studies have assessed if using spatial area averaging (based on known decorrelation length and/or time scales) can reduce the bias or increase the availability of satellite derived temperature data.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, previous studies have demonstrated biases in SST data when comparing it to in situ measurements within coastal areas (Smale and Wernberg, 2009;Lathlean et al, 2011;Stobart et al, 2016), with some studies recording up to 6 • C differences (Smit et al, 2013). These biases are due to contamination of the satellite processing due to the presence of coastal features such as the shoreline, estuaries and embayments as well as complex coastal dynamics such as tides and upwelling (Smit et al, 2013) that vary over short spatial scales. Despite this well documented bias of satellite SST data in coastal areas, no studies have assessed if using spatial area averaging (based on known decorrelation length and/or time scales) can reduce the bias or increase the availability of satellite derived temperature data.…”
Section: Introductionmentioning
confidence: 99%
“…SST, however, may not be available for coastal areas due to contamination in the satellite-derived images [noisier radar returns from land and sea (Brooks et al, 1990) and improper instrument corrections (Shum et al, 1998)]. In addition, previous studies have demonstrated biases in SST data when comparing it to in situ measurements within coastal areas (Smale and Wernberg, 2009;Lathlean et al, 2011;Stobart et al, 2016), with some studies recording up to 6 • C differences (Smit et al, 2013). These biases are due to contamination of the satellite processing due to the presence of coastal features such as the shoreline, estuaries and embayments as well as complex coastal dynamics such as tides and upwelling (Smit et al, 2013) that vary over short spatial scales.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the differences between the in situ and satellite measurements of coastal sea temperature have also been evaluated by other authors [13][14][15], where this error can be as large as 6 • C [15]. All of these papers specifically analyzed SST data retrieved from advanced very high-resolution radiometer (AVHRR) and/or moderate resolution imaging spectroradiometer The study area comprised three sections of Italian coastal waters (Figure 1a): the Manfredonia Gulf, Taranto Gulf, and the area close to Lesina Lagoon [42].…”
Section: Introductionmentioning
confidence: 99%